Reproductive Health Problems and Depression Levels of Women Living in Sanctuary Houses as a Result of Husband Violence - (:unkn) unknown (TAYLOR & FRANCIS INC, 2011)
We conducted this study to examine the reproductive health status and depression levels of women who live in sanctuary houses after being subjected to domestic violence. The total number of women in the study is 65. Data were collected via descriptive, violence, and women's reproductive health problems questionnaires and the Beck Depression Inventory (BDI). The women had experienced all kinds of extreme violence. As regards to reproductive health, the women had undergone several kinds of disorders such as menstrual irregularities, genital infection, and premenstrual syndrome. Based on the BDI cut-off values, it was concluded that all these women need medical treatment.
Keywords: DOMESTIC VIOLENCE; CONSEQUENCES